2016
DOI: 10.1039/c6sc02129h
|View full text |Cite
|
Sign up to set email alerts
|

Scandium-catalysed intermolecular hydroaminoalkylation of olefins with aliphatic tertiary amines

Abstract: A homoleptic scandium trialkyl complex in combination with a borate compound served as an excellent catalyst for the C–H addition of aliphatic tertiary amines to various olefins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 68 publications
1
46
2
Order By: Relevance
“…Hydroaminoalkylation of olefins with aliphatic tertiary amines was developed using a scandium catalyst. 63 β-Alkylation of the adamantane scaffold occurred with 1-(dimethylamino)adamantane (109) as the starting material in the presence of four equivalents of norbornene (Scheme 46). Presumably metalation of the adamantane framework, formation of a C-Sc bond, occurs during the course of the reaction.…”
Section: Scheme 44 β-Arylation Of a 1-(1-adamantyl)ethanone Oximementioning
confidence: 99%
“…Hydroaminoalkylation of olefins with aliphatic tertiary amines was developed using a scandium catalyst. 63 β-Alkylation of the adamantane scaffold occurred with 1-(dimethylamino)adamantane (109) as the starting material in the presence of four equivalents of norbornene (Scheme 46). Presumably metalation of the adamantane framework, formation of a C-Sc bond, occurs during the course of the reaction.…”
Section: Scheme 44 β-Arylation Of a 1-(1-adamantyl)ethanone Oximementioning
confidence: 99%
“…It was shown that in the presence of bulky vinylsilanes the linear product is isolated as a sole regioisomer using the commercially available Zr(NMe 2 ) 4 as the catalyst (complex G , Scheme 1). Such regioselectivity with vinylsilanes has also been reported by the Hou group using a scandium catalyst for the HAA reaction with tertiary amines, and computational investigations have revealed the important role of electronic effects in promoting regioselective reactivity [15, 16] . Motivated by the tolerance of N ‐silylbenzylamines in the HAA of alkenes we questioned whether N ‐aryl and N ‐alkyl benzylamine substrates could also furnish excellent reactivity and regioselectivities.…”
Section: Introductionmentioning
confidence: 67%
“…Therefore, as challenging as it seems to be, there is still a demand for applying this relevant methodology to obtain new compounds with known pharmacological properties. However, several molecules based on structural scaffolds related to important biological activities have been successfully achieved via scandium-catalyzed C-H activation [37][38][39][40][41]. Hou's group presented various studies on this theme [42,43], such as a notable work recently published in which they promoted a scandium-catalyzed intramolecular cyclization on benzimidazole substrates, via a C-H activation at the C-2 position (Scheme 2B).…”
Section: Review Scandium-catalyzed C-h Activationmentioning
confidence: 99%
“…A few years earlier, Hou and co-workers reported the very first metal-catalyzed C-H hydroaminoalkylation of tertiary amines using norbornene as the coupling partner [41]. For this method, the scandium catalyst that presented the best performance was a homoleptic trialkylscandium, [Sc-3] (Scheme 6B), instead of the usual cyclopentadienyl-containing dialkylscandium catalysts described so far in this review.…”
Section: Review Scandium-catalyzed C-h Activationmentioning
confidence: 99%